2010
DOI: 10.1682/jrrd.2009.11.0181
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported cognitive symptoms following mild traumatic brain injury are poorly associated with neuropsychological performance in OIF/OEF veterans

Abstract: Abstract-Mild traumatic brain injury (mTBI) is not uncommon among Operation Iraqi Freedom/Operation EnduringFreedom (OIF/OEF) veterans, and many individuals within this group report lingering cognitive difficulties following their injury. For Department of Veterans Affairs clinicians, an accurate assessment of cognitive symptoms is important in providing appropriate clinical care. Although self-assessment is commonly employed to screen for difficulties in cognitive functioning, little is known about the accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
99
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 44 publications
13
99
0
1
Order By: Relevance
“…In a sample of veterans with a history of mTBI, self-ratings on a neurobehavioral symptom checklist were compared with the results of a brief neuropsychological examination. Self-ratings of attention and thinking/organization were not significantly correlated with test findings, but were related to increased reporting of psychiatric symptoms [15].…”
Section: Introductionmentioning
confidence: 76%
“…In a sample of veterans with a history of mTBI, self-ratings on a neurobehavioral symptom checklist were compared with the results of a brief neuropsychological examination. Self-ratings of attention and thinking/organization were not significantly correlated with test findings, but were related to increased reporting of psychiatric symptoms [15].…”
Section: Introductionmentioning
confidence: 76%
“…Self-reported ratings of memory impairment were only modestly correlated (r = āˆ’.20) with verbal delayed recall and were unrelated to verbal immediate recall and delayed recall of non-verbal information (Spencer et al, 2010). Moreover, self-reported cognitive problems were positively correlated with the number of symptoms of depression, PTSD, and anxiety these Veterans endorsed (Spencer et al, 2010). These findings highlight the influence of psychological distress on subjective perceptions of cognitive difficulties following mTBI.…”
Section: Va Author Manuscriptmentioning
confidence: 82%
“…Specifically, subjective ratings of attention/ concentration and thinking/organization were unrelated to objective tests of these domains. Self-reported ratings of memory impairment were only modestly correlated (r = āˆ’.20) with verbal delayed recall and were unrelated to verbal immediate recall and delayed recall of non-verbal information (Spencer et al, 2010). Moreover, self-reported cognitive problems were positively correlated with the number of symptoms of depression, PTSD, and anxiety these Veterans endorsed (Spencer et al, 2010).…”
Section: Va Author Manuscriptmentioning
confidence: 87%
“…Historically, Veterans returning from war have reported cognitive complaints, which, in the vast majority of cases, are not attributable to TBI [26][27]. Cognitive postconcussive symptoms often lack objective neurocognitive findings, and studies in civilians have shown that these symptoms occur at similar rates in persons with mTBI as in those with no TBI [28][29].…”
Section: Memory and Attentionmentioning
confidence: 99%
“…In fact, mTBI had only a very modest additional effect on cognitive impairment when it co-occurred with PTSD and depression. Self-reported cognitive symptoms following mTBI have been shown to be poorly associated with neuropsychological performance in combat Veterans [26][27]31]. Moreover, neuropsychological deficits following mTBI typically resolve in weeks to months following the injury [32].…”
Section: Memory and Attentionmentioning
confidence: 99%